2018
DOI: 10.1021/acs.jmedchem.7b01345
|View full text |Cite
|
Sign up to set email alerts
|

Extra Sugar on Vancomycin: New Analogues for Combating Multidrug-Resistant Staphylococcus aureus and Vancomycin-Resistant Enterococci

Abstract: Lipophilic substitution on vancomycin is an effective strategy for the development of novel vancomycin analogues against drug-resistant bacteria by enhancing bacterial cell wall interactions. However, hydrophobic structures usually lead to long elimination half-life and accumulative toxicity; therefore, hydrophilic fragments were also introduced to the lipo-vancomycin to regulate their pharmacokinetic/pharmacodynamic properties. Here, we synthesized a series of new vancomycin analogues carrying various sugar m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 57 publications
1
52
0
Order By: Relevance
“…Noteworthy, the best vancomycin analogs show an improved balance in hydrophobicity and hydrophilicity, with the hydrophobic moiety likely contributing to an increased efficacy against vancomycin-resistance strains, while the hydrophilic moiety appears to compensate for the observed toxicity, eventually leading to analogs with improved therapeutic indices. These findings are in agreement with a recent study by Guan et al (2018) , reporting on the development of new vancomycin analogs. They introduced extra hydrophilic sugar moieties to eliminate the toxicity induced by the lipophilic substitutions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Noteworthy, the best vancomycin analogs show an improved balance in hydrophobicity and hydrophilicity, with the hydrophobic moiety likely contributing to an increased efficacy against vancomycin-resistance strains, while the hydrophilic moiety appears to compensate for the observed toxicity, eventually leading to analogs with improved therapeutic indices. These findings are in agreement with a recent study by Guan et al (2018) , reporting on the development of new vancomycin analogs. They introduced extra hydrophilic sugar moieties to eliminate the toxicity induced by the lipophilic substitutions.…”
Section: Discussionsupporting
confidence: 93%
“…In spite of the efficacy of modifications with lipophilic substituents, the latter may also result in long elimination half-lifes and accumulative toxicity. Recently, Guan et al (2018) reported that the introduction of hydrophilic substituents like sugar moieties counteracts the negative effects of lipophilic substituents, resulting in an enhanced efficacy, optimal pharmacokinetics and a lower toxicity. Modifications in the core structure of vancomycin, which comprises the binding site of vancomycin to D -Ala- D -Ala, have remained largely unexplored, as this requires total synthesis of the vancomycin analogs.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However,a fter over 50years of clinical use,vancomycin-resistant bacteria, including vancomycin-resistant S. aureus (VRSA) and Enterococci (VRE), have emerged and become new challenges in antibacterial treatment. [6] To tackle antibiotic resistance, various modification strategies have been applied to develop novel vancomycin derivatives,such as lipophilic modification on vancosamine, [7] ligand-binding enhancement, [8] attachment of membrane-disrupting fragments, [8c, 9] pyrophosphate-targeting designs, [10] and the modification of the vancomycincore structure by total synthesis. [9e, 11] Recently,acombined modification of lipophilic and cationic motifs on vancomycin has been used to enhance the ability of vancomycin to permeabilize the bacterial membrane,i ncluding vancomycin derivatives carrying C-terminal lipophilic quaternary ammonium moieties from the Halder group [9d] and carrying lysinerich lipopeptides from the Cooper group.…”
mentioning
confidence: 99%
“…121 Their rationale was that while the lipophilic substitutions on vancomycin enhance bacterial cell wall interactions, they also lead to long elimination half-life and accumulative toxicity, which might be alleviated by the addition of hydrophilic sugar units. They tested combinations of 12 different lipophilic substituents and 9 sugar residues, generating 24 analogs (including 3 that also included a C -terminal dimethylaminopropyl amide group).…”
Section: New Glycopeptide Derivativesmentioning
confidence: 99%
“…NMR studies of 19 bound to a Lipid II Ac 2 -Lys- d -Ala- d -Ala tripeptide showed indications of interactions with the new carbohydrate, supported by an H-bond seen in molecular modeling. 121 …”
Section: New Glycopeptide Derivativesmentioning
confidence: 99%